Modeling the partial equilibrium in the milk and dairy market in Ukraine - S. Kvasha; N. Davydenko; A. Ivanko; Z. Titenko (Global Journal of Environmental Science and Management)
The goals of the article are a definition of patterns of change in demand and supply of milk and dairy in the market of Ukraine and revealing the regularities of establishing of partial equilibrium state. The scientific methods which used in the process of the research: simulation was used for defining trends of supply and demand changing and their balancing in the dairy market; economic and statistical method was used for estimation of tendencies of production and consumption of dairy products in Ukraine; analysis and synthesis were used to find out the reasons that determine the trends of supply and demand changes; tabular and graphical methods were used for clearness of the image of the obtained research results; abstract-logical method was used for the formulation of conclusions. Results of the researching: Trends of demand and supply changes in the dairy market in the 2016 year was estimated. Specifics of establishing the state of partial equilibrium in that market were characterized relative to the main groups of its participants as producers and consumers. Development of methodological and practical aspects of features of establishing the state of market equilibrium in the dairy market, unlike existing, is based on a model basis is still actual. The practical significance of those results consists in working out of the tool of justification of managerial decisions for assessing the state and creating regulatory measures for sectoral development.